Effects of Low Volume Fraction of Polyvinyl Alcohol Fibers on the Mechanical Properties of Oil Palm Shell Lightweight Concrete - Yew, M.K.; Mahmud, H.B.; Ang, B.C.; Yew, M.C. (Hindawi Publishing Corporation, 2015)
This paper presents the effects of low volume fraction (Vf) of polyvinyl alcohol (PVA) fibers on the mechanical properties of oil palm shell (OPS) high strength lightweight concrete mixtures. The slump, density, compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity under various curing conditions have been measured and evaluated. The results indicate that an increase in PVA fibers decreases the workability of the concrete and decreases the density slightly. The 28-day compressive strength of oil palm shell fiber-reinforced concrete (OPSFRC) high strength lightweight concrete (HSLWC) subject to continuous moist curing was within the range of 43-49 MPa. The average modulus of elasticity (E) value is found to be 16.1 GPa for all mixes, which is higher than that reported in previous studies and is within the range of normal weight concrete. Hence, the findings of this study revealed that the PVA fibers can be used as an alternative material to enhance the properties of OPS HSLWC for building and construction applications.